Exposure to mass media medicine advertisements and practice of self- medication among Undergraduates of University of Ibadan (2023)
Self-medication has become a health care issue globally and concerns are not uncommon about the part being played by the mass media medicine advertisements in promoting its practice, especially among the youths. Few studies have investigated the correlation betM>een exposure to mass media medicine advertisements and self- medication among students from Nigerian universities. The study, therefore examined the influence of mass media medicine advertisements on self-medication among undergraduates of University of Ibadan. Cross-sectional survey was adopted as the research design while multi-stage sampling procedure was used in selecting 241 respondents across 8 departments. Structured questionnaire served as the instrument for data collection while descriptive statistics, Spearman rho and Pearson Chi- square were used to analyze the data. Majority (n=162; 67.2%) were exposed to mass media medicine advertisements 3 months prior to the study. Finding further showed a negative correlation between exposure to mass media medicine advertisements and self- medication practices among University of Ibadan undergraduates. The study concludes that there is needfor further studies to interrogate other plausible intervening variables that may be influencing self-medication among this cohort.